Case Report: Neurologic Presentation of West Nile Virus: Difficult Diagnosis - Manusov, Eron G.; Campuzano, Amalia Mora; Ahmed, Omar; Macias, Samantha; Gomez de Ziegler, Carolina; Munoz Monaco, Gerardo (Frontiers in Public Health, 2021)
West Nile virus infections have surged across the globe. South Texas, located on the path of bird migration, with Culex quinquefasciatus and other Culex species, and biotic primers that predispose the area to epidemics (floods, amplifying hosts, and lack of mosquito control and prevention) remains a highly endemic area for arbovirus spread. West Nile virus infection ranges from mild febrile illness to severe central nervous system involvement. The purpose of this report is to highlight complex presentations of WNV and how confounding presenting symptoms delay diagnosis. The secondary goal is to describe how pandemics, such as SARS-CoV-2, can overwhelm the system and result in medical decision bias errors.